2024
DOI: 10.1093/hmg/ddae013
|View full text |Cite
|
Sign up to set email alerts
|

Excessive tubulin glutamylation leads to progressive cone-rod dystrophy and loss of outer segment integrity

Rawaa Aljammal,
Thamaraiselvi Saravanan,
Tongju Guan
et al.

Abstract: Mutations in Cytosolic Carboxypeptidase-like Protein 5 (CCP5) are associated with vision loss in humans. To decipher the mechanisms behind CCP5-associated blindness, we generated a novel mouse model lacking CCP5. In this model, we found that increased tubulin glutamylation led to progressive cone-rod dystrophy, with cones showing a more pronounced and earlier functional loss than rod photoreceptors. The observed functional reduction was not due to cell death, levels, or the mislocalization of major phototransd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…This provided the first link between tubulin polyglutamylation and photoreceptor degeneration in humans. Recently, a mouse model lacking CCP5 showed that hyperglutamylation observed in this mutant leads to photoreceptor cell degeneration with altered outer segments (Aljammal et al, 2024). However, mechanisms of photoreceptor cell degeneration at play are not known.…”
Section: Introductionmentioning
confidence: 99%
“…This provided the first link between tubulin polyglutamylation and photoreceptor degeneration in humans. Recently, a mouse model lacking CCP5 showed that hyperglutamylation observed in this mutant leads to photoreceptor cell degeneration with altered outer segments (Aljammal et al, 2024). However, mechanisms of photoreceptor cell degeneration at play are not known.…”
Section: Introductionmentioning
confidence: 99%